Políticas da infância: relações dialógicas e possibilidades de auto (trans) formação na Unidade de Educação Infantil Ipê Amarelo/UFSM - Guedes, Querti Adriana (2023)
This research project is part of the Postgraduate Program in Public Policy and Educational Management - professional master's degree - and addresses the issue of Public Policy, being linked to research line 1 - Policy and Management of Basic and Higher Education; it dialogues about Teacher Training in the Unit of Early Childhood Education Ipê Amarelo. It has as a general goal to research in the scope of childhood public policies the formation of teachers from the perspective of dialogical relations and the possibilities of self (trans)formation through humanizing thought; deepening the idea of collaborative space in the educative process with young children. For specific objectives, it prioritizes: to reflect on the relationship of public policies and the practice of teacher training; to recognize the educational public policies outlined by government proposals related to teacher training from a historical-social view; to develop sharing with the proposal of training practice in the self/trans/formative perspective, based on the situations evidenced in the expectations and praxis of teachers; and finally, to understand the contributions and impacts of the processes of initial and continued training of teachers involved in early childhood education in the context of the research, raising the question: How to overcome traditional formative models in childhood school? In this thought, the project is based on a research of qualitative approach of the applied type, to be carried out in the Unity of Early Childhood Education Ipê Amarelo from UFSM, characterized by a research-action, dialoguing with Thiollent (2005), with the subjects of the management team and teachers, using the techniques of documentary research, with a questionnaire and observations. The theoretical referential is organized based on authors Kuhlmann (2003), Rosemberg (2002), Campos (1993), Kishimoto (2005), Faria (1989), Oliveira (2010), Tuan (1983) and as a deepening Bell Hooks (2020), Paulo Freire (1989) and Morin (2019). The idealized final product will be in e-book, and aims to present the results of the interactions with the training in school context. Thus, for data collection, a questionnaire will be used with the school's management team and teachers, based on Gil (1999). To analyze the data, Bardin's (1997) Content Analysis approach will be used.